INCREASING CIVICS LEARNING ACHIEVEMENT THROUGH THE USE OF RUKAPE LEARNING MEDIA BASED ON YOUTUBE IN CLASS VII SMPN 1 PANJALU - Teti Hindasah; Mukhamad Murdiono (Indonesian Institute for Counseling, Education and Theraphy (IICET), 2023)
This study aims to prove and analyze the increase in Civics learning achievement through the use of RUKAPE learning media based on YouTube for class VIIA students of Panjalu 1 Junior High School in the 2022-2023 academic year. This type of research uses classroom action research by developing a model from Stephen Kemmis & Robin Mc Taggart in the form of cycles of action planning, action implementation, observation, and reflection. The research subjects were 32 students. Data collection techniques using tests, observation, and documentation. The data analysis technique uses descriptive statistical analysis by looking for the average value, the percentage of learning success. Criteria for the success of the action for learning achievement is the complete limit of 75 (KKM = 75) and class completeness of 85%. The results showed that there was an increase in civics learning achievement in the initial conditions (initial ability test), cycle I, and cycle II. On the initial ability test score, the class average was only 62.5 with a class completeness of 15.6% and students who scored = 75 totaled 5 students. In cycle I there was an increase, namely the class average became 67.5 and class completeness increased to 50% (an increase of 34.3%) and students who scored = 75 totaled 16 students. Furthermore, in cycle II there was also an increase, namely the class average became 81 and the class completeness became 87.5% (an increase of 37.5%) and students who scored = 75 totaled 28 students. Based on these results it can be concluded that the use of RUKAPE learning media based on YouTube can improve civics learning achievement in class VII A students of SMP Negeri 1 Panjalu for the 2022-2023 academic year.